CITOYEN.NE.S Conversation en Français - Dolidon, Annabelle (Open textbook library., 2021)
CITOYEN.NE.S is a French language method for the conversation class at the intermediate/ advanced level. Content and activities are built around the concepts of diversity, inclusivity and equity, and engage students to practice French while questioning and participating in the world they live in – to be full citizens whatever their background, their race or their gender identity. As the French spelling of the title indicates, the book embraces écriture inclusive and uses it for instructions and general information for all students. The book is composed of five chapters covering various themes. None of them provides again basic vocabulary from first- and second-year French courses, like food and body parts. Instead, each chapter builds on students’ previous knowledge and takes them further to develop language and cultural skills. Each chapter presents a mix of vocabulary lists and activities, authentic documents and others that have been written for the book, based on research. Chapters end with creative activities and one overarching assignment that help students go deeper in topics of interest. Early chapters have two grammar reviews, later chapters only one.